2020
DOI: 10.33370/jpw.v22i02.436
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Word of Mouth dan Citra Merek Terhadap Loyalitas Pelanggan Smartphone Oppo Dimediasi Kepercayaan Merek

Abstract: Tujuan penelitian ini adalah untuk mengetahui pengaruh Word of Mouth dan citra merek terhadap loyalitas pelanggan smarthphone Oppo di Karawang melaui kepercayaan merek sebaga medisi. Populasi penelitian ini adalah pelanggan smarthphone Oppo di Karawang dan sampel yang diambil sebesar 102 orang. Metode analisis data penelitian ini adalah analisis jalur yang sebelumnya diuji dengan uji instrumen dan uji asumsi klasik. Hasil pengujian menunjukkan bahwa Word of Mouth dan citra merek berpengaruh terhadap loyalitas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 2 publications
2
3
0
5
Order By: Relevance
“…The higher the consumer's trust in a brand, the higher the loyalty (Haryono & Octavia, 2014). The results of this study are supported by the results of research conducted by (Huda & Nugroho, 2020) who found that there was an influence between a brand image on Oppo smartphone customer loyalty in a positive direction. Then the research conducted by (Putra & Ekawati, 2017) found that brand image has a positive and significant effect on customer loyalty for Vespa motorcycles in Denpasar.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The higher the consumer's trust in a brand, the higher the loyalty (Haryono & Octavia, 2014). The results of this study are supported by the results of research conducted by (Huda & Nugroho, 2020) who found that there was an influence between a brand image on Oppo smartphone customer loyalty in a positive direction. Then the research conducted by (Putra & Ekawati, 2017) found that brand image has a positive and significant effect on customer loyalty for Vespa motorcycles in Denpasar.…”
Section: Discussionsupporting
confidence: 81%
“…Another study on marketing communication variables found that marketing communication strategies had an effect on customer loyalty at Apotek K24 Mulyosari Surabaya (Dedy Ayub Wicaksono, 2018). Other research on brands was also conducted and found that there was an influence between a brand image on Oppo Smartphone Customer Loyalty in a positive effect (Huda & Nugroho, 2020). This study also encourages researchers to examine the customer loyalty of PT Calispo Multi Utama Medan in terms of its relationship to price, marketing communication, and brand factors.…”
Section: Introductionmentioning
confidence: 69%
“…Tujuan menginformasikan hal ini adalah agar pelanggan yang lain mendapatkan informasi tambahan atas produk yang telah dibelinya. Menurut Huda & Nugroho (2020) word of mouth merupakan kegiatan yang positif dan menguntungkan bagi perusahaan, karena tidak perlu dilakkan pengenal kembali kepada calon pelanggan lainnya atas kualitas produk yang telah dihasilkan. Sedangkan menurut Agustin et al, (2021) menyatakan bahwa word of mouth merupakan bentuk komunikasi yang dilakukan oleh setiap orang yang tujuannya menyampaikan informasi sebuah barang atau jasa kepada orang lain untuk diperoleh perhatian dari orang banyak yang harapannya orangorang itu percaya dan yakin terhadap produk yang dihasilkan.…”
Section: Word Of Mouthunclassified
“…Abror et al, (2020); Manyanga et al, (2022) dalam penelitiannya juga menjelaskan bahwa word of mouth dapat meningkatkan loyalitas pelanggan. Kekuatan dari word of mouth ada pada benar dan positifnya informasi yang disampaikan kepada orang lain (Huda & Nugroho, 2020). Orang yang mendengar informasi baik tentang sebuah produk atau jasa akan terdorong kembali untuk melakukan transaksi dikemudian hari (Akbari et al, 2016).…”
Section: Pengaruh Word Of Mouth Terhadap Loyalitas Pelangganunclassified
“…Therefore, the company will be known by many more people in the long run, beside that consumer will also become more loyal to the company. Positive information conveyed by others (word of mouth) will also make consumers more confident to continue using its halal products, proved that word of mouth affects customer loyalty (Huda & Nugroho, 2020). Loyal customers are customers who make repeat purchases, buy from various product lines from the same brand, recommend those brands to others, and also have competitor resistance products (Xie et al, 2019).…”
Section: Riri Oktarinimentioning
confidence: 99%